Pfizer-BioNTech COVID-19 Vaccine Tolerance in Allergic versus Non-Allergic Individuals - Nittner-Marszalska, Marita; Rosiek-Biegus, Marta; Kopeć, Agnieszka; Pawłowicz, Robert; Kosińska, Magdalena; Łata, Aleksandra; Szenborn, Leszek (Vaccines (Basel), 2021)
Individuals with a history of allergy are potentially at risk of suffering from adverse effects after COVID-19 vaccination. We sought to assess the tolerance towards the Pfizer-BioNTech vaccine in allergic patients. To address this issue, we used a questionnaire conducted on-line in a group of medical professionals who were vaccinated with the Pfizer-BioNTech vaccine. A total of 1808 respondents, out of whom 1707 received two doses of the vaccine, returned the questionnaire. Local reactions after injection were more frequent in allergic individuals after both doses (swelling p = 0.0003). Systemic adverse events (AE-SYS) occurred more often after the second than the first dose in both groups (allergic persons: 77.29% vs. 41.06%); vomiting and arthralgia occurred more often in allergic subjects (p = 0.0009). AE-SYS in allergic individuals lasted longer than in non-allergic ones after the first (p = 0.01) and the second dose (p = 0.0009). Allergic reactions after vaccination were reported more frequently in allergic subjects: after the first dose (p = 0.00001) and after the second dose (p = 0.001). Rhinitis was the most frequent symptom observed more often in allergic patients. No severe allergic reactions occurred during the full cycle of vaccination. Although the Pfizer-BioNTech vaccine is tolerated worse by allergic than non-allergic individuals, the occurring adverse symptoms are mild and do not preclude a successful completion of the vaccination cycle. The presence of symptoms suggestive of allergy does not constitute a condition of increased risk of developing clinically significant adverse events following Pfizer COVID-19 vaccination.